(untitled) (AYUSHDHARA, 2024)
Guillain-barre syndrome is a rare disorder in which the body’s immune system attacks nerves and causes damage to the peripheral nerves. The nerve injury often causes pain to precede muscle weakness that ascends rapidly from lower to upper limbs, loss of reflexes, Numbness, and Miller-Fisher syndrome presents with areflexia, and ophthalmoplegia, often with pupillary paralysis. The signs and symptoms of GBS can be correlated with Sarvangavata in our classics having symptoms like Chesta nivrutti, Ruja, Vaksthamba. In other systems of medicine, the line of treatment includes plasma exchange or intravenous immunoglobulin therapy, ventilatory support gives only symptomatic relief and the chance of re-occurrence will be higher, in such cases the Panchakarma chikitsa, plays an important role in correcting pathophysiology. Methodology: A single case study of male patient aged 16 years presents with bilateral upper limb weakness, Pain over forearm and legs, bilateral lower limb weakness, difficulty in closing the eyes, difficulty in swallowing, 10kg weight loss in a span of 3 months, the symptoms of GB syndrome was co-related with Sarvanga vata Vyadhi initially he was treated with Kosta Shodhana with Nimbamrutadi eranda taila and Agnilepa chikitsa for 7 days considering Kaphavruta vyana followed by the principles of Vatavyadhi chikitsa including Sarvanga abhyanga with Balashwagandha lakshadi taila followed by Shashtika shali pinda sweda, Yoga basti, Anuvasana with Ashwagandha ghrita, Niruha with Mustadi rajayapana with mamsa rasa (meat soup). Result: The patient was assessed with Guillain-Barré Syndrome Disability Scale (Hughes), the total score of the scale was 6. The score before treatment was 4 comes to 2 after treatment, thus we can conclude that Panchakarma treatment found a significant approach in managing GB syndrome.